The Principle Of Politeness In The Speech Act Is The Term “Reproach” - Ataboyev Isroiljon Mirza o‘g‘li (Academia One, 2024)
Politeness plays a vital role in human communication, serving as a cornerstone for displaying consideration and respect towards others through our words and behaviors. It holds immense significance in all forms of communication, even in situations involving accusations. Accusations, being sensitive and potentially confrontational, require the application of politeness principles to uphold social harmony and prevent unnecessary conflicts. This article aims to delve into the concept of politeness within the context of accusing others, exploring the utilization of politeness strategies to soften accusations and minimize the potential negative impact on the accused. Additionally, it will discuss the significance of face-threatening acts and the management of face in accusatory speech acts
Keywords: comprehend; accusations; positive face; negative faces